Foresight in the time of COVID-19 - Maria Isabella Gariboldi; Vivian Lin; Jessica Bland; Mallika Auplish; Amy Cawthorne (Elsevier, 2021)
Foresight methodologies enable individuals and organizations to envision different future scenarios and plan for greater future resilience. However, foresight is an underused methodology in the Western Pacific region for health policy development that could be extremely beneficial, among other areas, in the context of public health emergency response. We present lessons learned from the application of foresight methodologies through remote, agile think tank sprints to inform the World Health Organization (WHO) Western Pacific Regional Office's (WPRO) response to the COVID-19 pandemic. Four think tanks were set up in topic areas of interest. The think tanks used a six-step foresight methodology to develop scenarios for the pandemic in an 18-month horizon. Backcasting was used to generate recommendations for WHO response and support for countries. This case study demonstrates the value of using foresight methodologies in public health, and specifically in the context of a public health emergency, and its ability to inform more context-appropriate and future-proof responses. Funding: Japan.